A new NLRP5 mutation causes female infertility and total fertilization failure. (4th March 2021) - Li, Mingzhao; Jia, Miaomiao; Zhao, Xiaoli; Shi, Rong; Xue, Xia
Abstract: Objective: The genetic reasons of total fertilization failure (TFF), especially regarding suspected oocyte-related factors, are largely unknown. Only PLCZ1, TLE6 and WEE2 mutations have been shown to result in human fertilization failure. The aim of this study is to report a new NLRP5 mutation which causes female infertility and total fertilization failure Methods: A patient presenting TFF after two failed cycles was included. In the first cycle, 13 oocytes were obtained, all of which were inseminated by IVF, but there was no sign of fertilization. In the second cycle, 11 oocytes were obtained, 8 of which were matured; however, none were fertilized upon ICSI and ICSI-AOA. Peripheral blood samples were taken from the patient and her family members. The whole-exome sequencing was performed on them. Results: We identified two heterozygous missense variants NLRP5 (NM_153447.4: c.1598G > C and 1919 T > G; p.Arg533Pro and Leu640Arg) which could cause the incidence of TFF. The first mutation of c.1598G > C (p.Arg533Pro) was inherited from her father and the second mutation of c.1919T > G (Leu640Arg) was inherited from her mother. The sister with normal fertility did not carry these variants. Conclusions: A new NLRP5 mutation causes female infertility and the incidence of TFF.